2021
DOI: 10.1049/gtd2.12157
|View full text |Cite
|
Sign up to set email alerts
|

Charge migration of multilayer oil paper on the process of partial discharge under AC voltage

Abstract: As one of the main reasons for the deterioration of Nomex paper and charge migration, partial discharge (PD) plays a critical role during PD degradation. In this study, the PD characteristics of multilayer oil paper are focused on. In order to explore the characteristics of charge migration, the experiments of the relative permittivity, conductivity, isothermal surface potential decay, scanning electron microscopy and Fourier infrared spectroscopy have been carried out. The results show that the discharge bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The impurities adsorbed on the surface are frequently considered to be the cause of physical traps [33]. The energy level of the physical traps is shallow, frequently less than 0.3 eV [34]; therefore, the increase of the physical traps will shift the distribution of the surface traps towards the shallow ones; in contrast, owing to the break of molecular chains and bonds during aging, the surface roughness of pressboard becomes larger and the surface area increases; therefore, the covalent bond for chemical adsorption on the pressboard surface increases accordingly [35], and new chemical defects are introduced [36]. The energy levels of chemical trap are significantly deeper than those of the physical trap, but are generally less than 1.0 eV [33], resulting in the shift of energy levels of pressboard surface to those of deep traps.…”
Section: Discussionmentioning
confidence: 99%
“…The impurities adsorbed on the surface are frequently considered to be the cause of physical traps [33]. The energy level of the physical traps is shallow, frequently less than 0.3 eV [34]; therefore, the increase of the physical traps will shift the distribution of the surface traps towards the shallow ones; in contrast, owing to the break of molecular chains and bonds during aging, the surface roughness of pressboard becomes larger and the surface area increases; therefore, the covalent bond for chemical adsorption on the pressboard surface increases accordingly [35], and new chemical defects are introduced [36]. The energy levels of chemical trap are significantly deeper than those of the physical trap, but are generally less than 1.0 eV [33], resulting in the shift of energy levels of pressboard surface to those of deep traps.…”
Section: Discussionmentioning
confidence: 99%
“…The previous investigations of PD damage characteristics in oil-impregnated Nomex paper under AC [13][14][15] indicated that the creepage tree phenomenon caused by dv/dt is observed. However, it can be found that the PD damage mechanism under HF stress is different.…”
Section: The Influence Of Bulk Effectsmentioning
confidence: 97%
“…Thirumurugan et al 12 studied the effect of different solid and liquid insulation materials on the surface PD characteristics, and discussed the topography and composition of samples during PD. Li et al [13][14][15] expounded the PD characteristics of oil paper and trap parameters of PD degradation, and concluded that surface charge and trap distribution are helpful in clarifying the PD mechanism. However, the above-mentioned literature mainly studied PD damage characteristics and the mechanism of oil-paper insulation under AC voltage.…”
Section: Introductionmentioning
confidence: 99%